HUBUNGAN KETERAMPILAN MENGAJAR GURU MENURUT PERSEPSI SISWA DENGAN MOTIVASI BELAJAR DAN HASIL BELAJAR MATEMATIKA SISWA - Suminto Suminto (Universitas Muhammadiyah Pringsewu, 2018)
Abstract This study aims to determine the relationship of teacher teaching skills according to the perception of students with learning motivation and student learning outcomes. This research uses documentation and questionnaire method, where documentation method is used to obtain learning result data, while questionnaire to obtain teacher skill teaching data according to student perception and learning motivation. The population in this study are students of class VII SMP Negeri 1 Banyumas academic year 2017-2018. Sample determination by random sampling technique Data analysis using correlation analysis of pearson product moment and multiple correlation. From the results of the analysis shows that there is a relationship between teaching skills of teachers according to students' perceptions. There is a relationship of learning motivation with student learning result of mathematics. And there is correlation of teacher teaching skill according to student perception and learning motivation with student mathematics learning result.Thus the teacher's teaching skills and student motivation need to be considered to improve students' mathematics learning outcomes.   Keywords: teaching skills, pupil perception, motivation and learning outcomes